2015
DOI: 10.1002/jcph.500
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' and general practitioners' pharmacology knowledge and pharmacotherapy skills

Abstract: Understanding differences in the pharmacology knowledge and pharmacotherapy skills of pharmacists and physicians is vital to optimizing interprofessional collaboration and education. This study investigated these differences and the potential influence of work experience. The pharmacology knowledge and pharmacotherapy skills of pharmacists, general practitioners (GPs), and trainees were compared, using a written assessment; 294 participants were included. Overall scores (mean ± SD) ranged from 69.3% ± 6.5% to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Although a gold standard for sufficient knowledge is not available, we believe, in line with the UK Prescribing Safety Assessment, that medical graduates should have high test scores (≥80–90%) to be able to prescribe safely and effectively after graduation. In particular, students had a poor knowledge of drug interactions and contraindications (50%), as also reported for junior and senior doctors . This poor knowledge could be because the quantity and quality of undergraduate clinical pharmacology teaching is inadequate, as implied by the students.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although a gold standard for sufficient knowledge is not available, we believe, in line with the UK Prescribing Safety Assessment, that medical graduates should have high test scores (≥80–90%) to be able to prescribe safely and effectively after graduation. In particular, students had a poor knowledge of drug interactions and contraindications (50%), as also reported for junior and senior doctors . This poor knowledge could be because the quantity and quality of undergraduate clinical pharmacology teaching is inadequate, as implied by the students.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, students had a poor knowledge of drug interactions and contraindications (50%), as also reported for junior and senior doctors. 13 This poor knowledge could be because the quantity and quality of undergraduate clinical pharmacology teaching is inadequate, as implied by the students. Despite the growing digital support (e.g., apps, websites), clinical pharmacology remains a target for educational improvement, because an adequate knowledge of drug 0% 25% 50% 75% 100%…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…When medicines reviews are scheduled, giving pharmacists and prescribers a copy of ADRe alongside the MAR chart links residents’ problems to the clinical goal of freedom from ADRs (Fig 3) [58,59]. When reviewing medicines, pharmacists and doctors rarely have time to interview patients about every possible adverse effect of all their medicines, many residents are non-verbal, and the resident’s key carer is often off-duty, due to 12 hour shift patterns.…”
Section: Discussionmentioning
confidence: 99%
“…CPs are well-positioned to collaborate and communicate with GPs and patients if an antimicrobial prescription is believed to be inappropriate [8,9,11]. Multiple studies [12][13][14] reported that providing recommendations on the choice, and dose of antimicrobial prescriptions and ability to assess appropriateness of GPs' antimicrobial prescriptions by CPs depend on adequate knowledge, skills and positive attitudes of CPs towards AMS. CPs' ability to implement AMS in collaboration with GPs has been shown to depend on the context where they work [15,16].…”
Section: Introductionmentioning
confidence: 99%